ANALISIS PRAKTIK PENGGUNAAN MERK DAGANG OLEH RESELLER BATIK COLET DI JATIPELEM JOMBANG - Refi Aisyah Sakirul Arifah; Norma Fitria (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Trademark protection in works of art, especially batik, is not only limited to positive law, but can also be studied through Islamic Business Law. As happened in the Batik Colet Industry in Jatipelem Jombang, namely the violation of trademark rights by resellers, where there are resellers who copy and change the motifs that are characteristic of batik colet with other motifs and colors. The focus of this study is: How is the Practice of Using Trademarks by Batik Colet Resellers in Jatipelem Jombang and How is the Perspective of Islamic Business Law on the Practice of Using Trademarks by Batik Colet Producers in Jatipelem Jombang. This study was conducted using a conceptual study approach method, then analyzed using an Islamic business law perspective. The results of this study obtained: 1) The use of trademarks by resellers in Batik New Colet applies a consignment system, in practice there are resellers who plagiarize, by not including their own brand name when marketing their batik products, but they use the Batik Colet brand name, with the aim of keeping the price of batik affordable with materials that are not the same quality as the original Batik Colet brand. 2) In Islamic Business, the act of plagiarizing trademarks on Batik New Colet is an act that seizes ownership rights (huquq al-maliyah)..